Kajian Perencanaan Tata Ruang untuk Memfasilitasi Kegiatan Non-Pertanian di Kecamatan Sukorejo, Kabupaten Kendal - Ratika Tulus Wahyuhana; Agung Sugiri (Department of Urban and Regional Planning, Diponegoro University, 2014)
Rural non-farm sector is potential to alleviate poverty and improve rural people’s welfare; however, its development is less encouraged by the government policy, especially the regional spatial plans in Indonesia (Sugiri, et al. 2011). The situation also occurs in Sukorejo District (Kecamatan) of Kendal Regency (Kabupaten) as a potential region for developing rural non-farm sector. This study is aimed at answering the research question of: